Efficacy and safety of cilostazol in decreasing progression of cerebral white matter hyperintensities—A randomized controlled trial. Issue 1 (27th December 2022) - Ip, Bonaventure Y. M.; Lam, Bonnie Y. K.; Hui, Vincent M. H.; Au, Lisa W. C.; Liu, Mandy W. T.; Shi, Lin; Lee, Vivian W. Y.; Chu, Winnie C. W.; Leung, Thomas W.; Ko, Ho; Mok, Vincent C. T.
Abstract: Introduction: Cerebral small vessel disease (SVD) is an important cause of dementia that lacks effective treatment. We evaluated the efficacy and safety of cilostazol, an antiplatelet agent with potential neurovascular protective effects, in slowing the progression of white matter hyperintensities (WMHs) in stroke‐ and dementia‐free subjects harboring confluent WMH on magnetic resonance imaging (MRI). Methods: In this single‐center, randomized, double‐blind, placebo‐controlled study, we randomized stroke‐ and dementia‐free subjects with confluent WMHs to receive cilostazol or placebo for 2 years in a 1:1 ratio. The primary outcome was change in WMH volume over 2 years. Secondary outcomes were changes in brain volumes, lacunes, cerebral microbleeds, perivascular space, and alterations in white matter microstructural integrity, cognition, motor function, and mood. Results: We recruited 120 subjects from October 27, 2014, to January 21, 2019. A total of 55 subjects in the cilostazol group and 54 subjects in the control group were included for intention‐to‐treat analysis. At 2‐year follow‐up, the changes in WMH volume were not statistically different between cilostazol treatment and placebo (0.3±1.0 mL vs −0.1±0.8 mL, p = 0.167). Secondary outcomes, bleeding and vascular events, were also not statistically different between the two groups. Discussion: In this trial with stroke‐ and dementia‐free subjects with confluent WMHs, cilostazol did not impact WMH progression but demonstrated an acceptable safety profile. Future studies should address the treatment effects of cilostazol on subjects at different clinical stages of SVD.